Characterization of herbal teas containing lime flowers – Tiliae flos by HPTLC method with chemometric analysis. (1st June 2021) - Melnyk, Natalia; Pawłowska, Karolina A.; Ziaja, Maria; Wojnowski, Wojciech; Koshovyi, Oleh; Granica, Sebastian; Bazylko, Agnieszka
Highlights: Fast and sensitive HPTLC method for the differentiation of Tilia sp. was developed. An algorithm for visual-based confirmation of pharmacopeial species was established. An SVM-based machine learning method was applied for the evaluation of HPTLC data. Abstract: Linden trees are a source of food products called lime flowers ( Tiliae flos ), traditionally used in the form of infusion for the treatment of feverish colds and coughs. Lime flowers should include flowers of Tilia cordata Mill, T.x europaea L., and T. platyphyllos Scop. or a mixture of these. The aim of current research was to establish a fast, sensitive HPTLC (high-performance thin-layer chromatography) method that would allow the differentiation of material obtained from five species of lime occurring in Europe. The fingerprints for distinguishing these species were established, as well as a key for identification based on a visual evaluation of chromatograms. The results obtained were also subjected to chemometric analyses. It was shown that each species contains characteristic compounds i.e. linarin that can be used for their identification. The method developed can, in theory, be introduced for the quality control or authentication of linden flowers on the European market.